The good, the bad, and the spooky - John, Jory; Oswald, Pete; Joshaghani, Saba (New York, NY : Harper, an imprint of HarperCollins Publishers, 2021)
When Bad Seed cannot find an amazing costume for Halloween night, he postpones trick-or-treating for everyone else until he finds the perfect one.
The bad seed presents.
May include stickers.
2.2
K-3
Keywords: Seeds -- Juvenile fiction; Halloween -- Juvenile fiction; Human behavior -- Juvenile fiction; Conduct of life -- Juvenile fiction; Humorous stories; Seeds -- Fiction; Halloween -- Fiction; Behavior -- Fiction; Conduct of life -- Fiction; Humorous fiction